2010
DOI: 10.1111/j.1750-3639.2010.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher Soluble Amyloid β Concentration in Frontal Cortex of Young Adults than in Normal Elderly or Alzheimer's Disease

Abstract: Little is known about the relationship between soluble amyloid beta (Abeta) and age. We have measured soluble and insoluble Abeta by enzyme-linked immunosorbent assay (ELISA) in post-mortem frontal cortex in normal brains (16-95 years) and AD. Insoluble Abeta increased with age, and was significantly higher in Alzheimer's disease (AD) than age-matched controls. However, levels of soluble Abeta declined with age and were significantly greater in younger adults than older adults with or without AD. In AD, insolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 41 publications
(61 reference statements)
3
47
0
Order By: Relevance
“…Aβ production gradually shifts from soluble to insoluble Aβ peptides with increasing age [34], which may shorten the time from occurrence of pathological amyloid metabolism to onset of clinical symptoms. A third reason could be that Aβ is a less important cause of dementia in the oldest old.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ production gradually shifts from soluble to insoluble Aβ peptides with increasing age [34], which may shorten the time from occurrence of pathological amyloid metabolism to onset of clinical symptoms. A third reason could be that Aβ is a less important cause of dementia in the oldest old.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was reported that the level of soluble oligomeric Aβ in frontal cortex of young adults is higher than that of elderly people or Alzheimer’ disease patients using ELISA experiments (Halmond et al, 2010); potentially calling into question a relationship between oligomeric Aβ (as measured by the ELISA) with Alzheimer disease pathogenesis. In this study we observed that the level of HMW Aβ from TBS-soluble fraction is under-estimated in ELISA experiments due to a possible masking effect either by itself or interacting molecules, and the treatment with 8 M Guanidine-HCl increases the measured concentration of Aβ in HMW Aβ fractions using our specific ELISA conditions (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…We prepared soluble and insoluble (guanidine‐extractable) fractions of the homogenates for Aβ measurement as reported in previous studies 1, 5, 32, 55, 56, 57, 58.…”
Section: Methodsmentioning
confidence: 99%